2017
DOI: 10.1021/jacs.6b13029
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Copper Hydride-Catalyzed Markovnikov Hydrosilylation of Vinylarenes and Vinyl Heterocycles

Abstract: We report a highly enantioselective CuH-catalyzed Markovnikov hydrosilylation of vinylarenes and vinyl heterocycles. This method has a broad scope and enables both the synthesis of isolable silanes and the conversion of crude products to chiral alcohols. Density functional theory calculations support a mechanism proceeding by hydrocupration followed by σ-bond metathesis with a hydrosilane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(76 citation statements)
references
References 45 publications
0
76
0
Order By: Relevance
“…loss before C–C bond formation. In this latter scenario, higher allylphosphate concentration should lead to faster alkylation and the loss in kinetic selectivity would be diminished 9 . Indeed, whereas 2g was formed in 64% e.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…loss before C–C bond formation. In this latter scenario, higher allylphosphate concentration should lead to faster alkylation and the loss in kinetic selectivity would be diminished 9 . Indeed, whereas 2g was formed in 64% e.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the disclosure corresponding to the two-catalyst protocol 2 there is no mention of allyl–boron additions to electron-rich aryl alkenes or those involving more hindered (e.g., 2-substituted) electrophiles. Furthermore, enantioselective Cu–B(pin) or Cu–H additions with electron-deficient aryl olefins are either not mentioned 4,5,6,7,8 or found to be less enantioselective 9,10,11,12 (e.g., halo-, trifluoromethyl- or ester-substituted). It is unclear why enantioselectivity is lower with some substrates or at times depends on electrophile identity despite the fact that the Cu–B(pin)/Cu–H addition step is the stereochemistry-determining (e.g., 94% e.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral organosilanes have interesting properties because of the presence of as ilicon having ap articular physical and electronic nature,and they have attracted increasing attention in recent years.Inparticular,chiral organosilanes are used in organic synthesis, [1] materials science, [2] agroscience, [3] and medicinal chemistry. [4] Considerable effort has been devoted to this field, and many elegant catalytically asymmetric approaches for the synthesis of chiral organosilanes have been successfully developed, including asymmetric hydrosilylation of alkenes and alkynes, [5] asymmetric silicon hydride bond insertions, [6] desymmetrization of silanes, [7] asymmetric addition to b-silyl unsaturated carbonyls, [8] and asymmetric silyl conjugated addition. [9] Notably,m ost of the aforementioned methods have rely on transition metals as catalysts.In contrast, an organocatalyzed approach for the synthesis of chiral organosilanes has not been well explored.…”
mentioning
confidence: 99%
“…and enantioselectivity (99 % ee)w hen the more sterically hindered aminoindanolderived triazolium pre-catalyst B [16a] was used. Next, several bases were investigated, with Cs 2 CO 3 proving to be the best choice (entries [2][3][4][5][6][7][8]. Subsequent solvent screening revealed that 1,4-dioxane was the most effective,thus providing access to 3a in up to 98 %yield without any loss in d.r.oree values (entries [9][10][11][12].…”
mentioning
confidence: 99%